Eicosapentaenoic Acid from Porphyridium Cruentum: Increasing Growth and Productivity of Microalgae for Pharmaceutical Products - Maryam Asgharpour; Brigitte Rodgers; Jamie A. Hestekin (Energies, 2015)
An alternative source of eicosapentaenoic acid (EPA) or omega-3 could be microalgae lipids instead of fish oils. However, EPA and lipid contents extracted from microalgae vary at different growth conditions. Therefore, it is of paramount importance to optimize the growth conditions of microalgae to maximize EPA production. In this paper, the effects of temperature (16 °C and 20 °C), light intensity (140 µE m−2 s−1 and 180 µE m−2 s−1) and nitrate level (0.075, 0.3, 0.5, and 0.7 g/L) on the cell growth, lipid productivity, and omega-6/omega-3 ratio of Porphyridium cruentum, one of the most promising oil-rich species of microalgae, are investigated. The ratio of the fatty acids with omega-6 and omega-3 groups at various growth conditions were compared, since an appropriate proportion of ω-6 (arachidonic acid (ARA)) to ω-3 (EPA) is vital for healthy nutrition. Lower EPA production and consequently a higher ARA/EPA ratio occurred when 5% CO2/air was utilized as CO2 supplementation compared to pure CO2. The highest EPA (13.08% (w/w) of total fatty acids) and biomass productivity (143 mg L−1 day−1) was achieved at 140 µE m−2 s−1, 20 °C, and 0.3 g/L nitrate, while lipid content was the lowest (0.5% w/w) at this condition. The optimal condition with minimum ARA/EPA ratio (2.5) was identified at 20 °C, 140 µE m−2 s−1, and 0.5 g/L nitrate concentration.